(untitled) (Journal of Natural Language and Linguistics, 2024)
This paper is aiming to discover the paths that enable teachers to manage their work with students in the classroom. To be an efficient teacher means to know with what and how to motivate students to learn. Teacher as an efficient classroom manager needs to have skills to plan and prepare the education process, know how to organize the teaching and how to guide the class. An efficient teacher moreover needs establish positive classroom climate and working discipline. Also, teacher should be able to evaluate the progress of the students and self-evaluate his own work. The main focus was on library sources to conduct this study, collect related materials, and achieve the objectives of the study. Five books and five articles used as significant materials in this study. Analyses of results show that there is a deficit of classroom management skills among teachers, which is due moreover to some lapses in initial education of teachers. Teacher should also involve students in making rules and regulations that guide them. It concluded that students will not gain anything unless there is order in the classroom. Order can be achieved if the students are treated fairly, held responsible for their action and gainfully occupied. The more occupied the students are, the less time they have to engage in acts of indiscipline.